Deficits of Facial Emotion Recognition in Elderly Individuals with Mild Cognitive Impairment. - Ju, Eun-Yoo; Kim, Chae Yoon; Choi, Baek-Yong; Ryoo, Seung-Woo; Min, Jin-Young; Min, Kyoung-Bok (Dementia & Geriatric Cognitive Disorders, 2024)
Introduction: The study of facial emotion recognition is under-explored in subjects with mild cognitive impairment (MCI). We investigated whether deficits in facial emotion recognition are present in patients with MCI. We also analyzed the relationship between facial emotion recognition and different domains of cognitive function. Methods: This study included 300 participants aged 60 years or older with cognitive decline. We evaluated 181 MCI and 119 non-MCI subjects using the Seoul Neuropsychological Screening Battery-Core (SNSB-C) and facial emotion recognition task using six facial expressions (anger, disgust, fear, happiness, sadness and surprise). A Generalized Linear Model (GLM) was used to assess the association between cognitive performance and accuracy of facial emotion recognition and to compare facial emotion recognition in the MCI group based on the impairment of five different domains of cognitive function. The model was adjusted for age, sex, years of education, and depressive symptoms. Results: Patients with MCI had a lower score for accurately recognizing total facial emotion (0.48 vs. 0.53; ρ = 0.0003) and surprise (0.73 vs. 0.81; ρ = 0.0215) when compared to cognitively healthy subjects. We also discovered that frontal/executive function domain (Digit Symbol Coding [DSC, 0.38 vs. 0.49; p < 0.0001], Controlled Oral Word Association Test [COWAT, 0.42 vs. 0.49; p = 0.0001], Korean-Trail Making Test [K-TMT, 0.37 vs. 0.48; p = 0.0073], Korean-Color Word Stroop Test [K-CWST, 0.43 vs. 0.49; p = 0.0219]) and language domain (Korean-Boston Naming Test [S-K-BNT, 0.46 vs. 0.47; p = 0.003]) were statistically associated with the deficits of facial emotion recognition in patients with MCI. Conclusion: We observed a significant association between deficits in facial emotion recognition and cognitive impairment in elderly individuals.